IMPLEMENTASI KEBIJAKAN PROGRAM PENERIMAAN PESERTA DIDIK BARU SISTEM ZONASI DI SMA NEGERI SE KOTA BANDA ACEH - Ulfa Jazila; Daska Azis; Novia Zalmita (Jurnal Pendidikan Geosfer, 2021)
The zoning system acceptance of new students was determined based on the administrative area of the sub-district, while the existence of senior high school in Banda Aceh City was not evenly distributed in each sub-district. The formulation of the problem in this study is how to implement the policy of the new student admissions program in the zoning system in senior high school in Banda Aceh City? The purpose of the study was to determine the implementation of the zoning system for new student admissions program policies in senior high school in Banda Aceh. This research uses descriptive quantitative method. The population in this study were all Public High Schools in Banda Aceh. Sampling using purposive sampling technique, which is based on the criteria of schools that apply the zoning system acceptance of new students and accredited. Data collection using a questionnaire with the Guttman scale. The research instrument was declared valid and reliable. It was concluded that the implementation of policy on the zoning system acceptance of new students at the Banda Aceh City Senior High School was generally well implemented, supported by good communication between several parties involved, sufficient and competent resources, the characteristics of program implementers who are able to commit themselves to carrying out their duties and a flexible bureaucratic structure